ISOLASI DAN OPTIMASI PERTUMBUHAN BAKTERI PENGHASIL BIOFLOKULAN DARI LUMPUR AKTIF LIMBAH CAIR INDUSTRI UDANG DAN GURITA BEKU - , BUDI MULYARA, Dr. Ir. Latif Sahubawa, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fish processing wastewater containing high suspended solids and very difficult to be precipitated so if released into the environment is bad for the survival of aquatic organisms. To solve these problems, needs a safe and biodegradable flocculant. EPS ( Extracellular Polymeric Substances) is a type of bioflocculant produced by bacteria play an important role in floc formation. The aims of this research were to isolate and optimize flocculation activity of activated sludge from frozen shrimp and octopus wastewater. There were 29 bacteria (22 bacteria from clarifier 1